The pragmatics of morphological negation: pejorative and euphemistic uses of the prefix non- in French - Dugas, Edwige (Taikomoji kalbotyra, 2014)
In this paper I examine a particular type of morphological negation in French, namely non- prefixation on nominal bases (e.g. non-violence ‘nonviolence’). Drawing on a wide range of authentic examples from the Trésor de la Langue Française informatisé (TLFi), the French literary database Frantext and the internet, I show that although the basic meaning of non- prefixation is negation, the nouns prefixed by non- (abbreviated as [non-N]N) may carry an additional nuance, which can be pejorative or euphemistic; hence the hypothesis defended in this paper that the prefix non- can also serve pragmatic purposes.After having briefly described the morphological and semantic variety of nominal lexemes which can be the input of non- prefixation, I show that [non-N]N can have three different readings, namely what I call the “complementary” interpretation (e.g. les Italiens et les non-Italiens aiment la cuisine italienne ‘Italians and non-Italians like Italian cuisine’), the “ontological” interpretation (e.g. Toute sa vie durant, Gandhi est demeuré convaincu du bien-fondé de la non-violence ‘For all his life, Gandhi was convinced of the legitimacy of nonviolence’), and the “contrary interpretation” (e.g. Les fleurs, je m’en fiche. Serais-je une non-femme? ‘Flowers, I don’t care! Could I be a nonwoman?). In the second section, I describe the pejorative and euphemistic uses of [non-N]N. The pejorative useshave been noticed by several authors (a.o. Gaatone 1971, 1987, Di Sciullo and Tremblay 1993, 1996 for French, Zimmer 1964, Algeo 1971, Bauer 1983, Horn 1989 for English); I show that these uses arise when the [non-N]N have a contrary interpretation and that they are quite frequent. I also emphasize the importance of the discourse context compared to the semantics of the base noun. Then I address the euphemistic uses of [non-N]N, which are linked to the ontological interpretation, and which are more constrained and thus less frequent; I note that these uses function almost as a politeness device. The fourth section provides an attempt to draw a parallel between certain uses of [non-N]N and the polemic and metalinguistic uses of sentential negation, as they have been described by Ducrot (1980, 1984) and Horn (1985, 1989).
Keywords: pragmatics; français; non-; morphology; negation; semantics